Reported food-related symptoms and food allergen sensitization in a selected adult population in Hyderabad, India: A hospital-based survey - Priyanka Dadha, PhD; Sai Nimmagadda, MD; Carina Venter, PhD, RD; Ruchi Gupta, MD, MPH; Putcha Uday Kumar, MD; Christopher M. Warren, PhD (Journal of Allergy and Clinical Immunology: Global, 2024)
Background: Research on reported food-related triggers of atopic disease in South Asian adults is lacking despite the region’s large population and the global significance of allergic diseases. Objectives: The study aimed to identify prevalent local food items and assess allergic sensitization rates to potential trigger foods for atopic diseases via skin prick and specific IgE testing. Methods: The study began with a pilot survey of 100 subjects recruited from 4 hospitals in Hyderabad, India, focusing on foods perceived to relate to asthma, allergic rhinitis, atopic dermatitis, urticaria, and gastrointestinal allergic symptoms. A subsequent main study evaluated 2010 participants, 1754 of whom were diagnosed with an aforementioned atopic disease and who reported allergic symptoms related to any of 77 foods identified in the pilot study. Ultimately 1622 patients who consented to skin prick and specific IgE testing and who reported at least 1 food item triggering allergic diseases were included in the final analysis. Results: Among 1622 patients (average age, 42.6 ± 12.9 years; 55.5% male), asthma was the most commonly diagnosed atopic disease (26.4%), with itching and rash being frequently reported symptoms (22.7%). Notably, 94.9% of patients had total serum IgE > 144 kU/L. Chickpea, cabbage, eggplant, walnut, cumin, and betel leaf were the most commonly reported trigger foods. Conclusion: In this sample of South Indian adults diagnosed with allergic disease, reported food triggers were most commonly local dietary staples, while reported reactions to priority allergens like peanut and sesame were conspicuously absent. Observed concordance between patient-reported food triggers and sensitization to reported food triggers was low, highlighting the need for improved clinical evaluation of suspected triggers.